2016
DOI: 10.1016/j.dam.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Remoteness and distance eigenvalues of a graph

Abstract: Let G be a connected graph of order n with diameter d. Remoteness ρ of G is the maximum average distance from a vertex to all others and ∂ 1 ≥ · · · ≥ ∂ n are the distance eigenvalues of G. In [1], Aouchiche and Hansen conjectured that ρ + ∂ 3 > 0 when d ≥ 3 and ρ + ∂ ⌊ 7d 8 ⌋ > 0. In this paper, we confirm these two conjectures. Furthermore, we give lower bounds on ∂ n + ρ and ∂ 1 − ρ when G ≇ K n and the extremal graphs are characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The spectrum of distance matrix, arose from a data communication problem studied in [7] by Graham and Pollack in 1971, has been studied extensively (see [1,9,10,11,12,13,22]). The eigenvalues, eigenvectors and spectrum of D(G) are the D-eigenvalues, D-eigenvectors and D-spectrum of G, respectively.…”
mentioning
confidence: 99%
“…The spectrum of distance matrix, arose from a data communication problem studied in [7] by Graham and Pollack in 1971, has been studied extensively (see [1,9,10,11,12,13,22]). The eigenvalues, eigenvectors and spectrum of D(G) are the D-eigenvalues, D-eigenvectors and D-spectrum of G, respectively.…”
mentioning
confidence: 99%
“…Furthermore, they also proposed two conjectures. Lin et al [ 12 ] confirmed these two conjectures. They also gave lower bounds on and when and the extremal graphs were characterized.…”
Section: Introductionmentioning
confidence: 75%
“…Recently, the distance matrix of a graph has received increasing attention. Aouchiche and Hansen [2] and Lin, Das and Wu [12] proved some results on the relations between the distance eigenvalues and some graphic parameters. Lin [11] proved an upper bound on the least distance eigenvalue of a graph in terms of it order and diameter.…”
Section: Introductionmentioning
confidence: 94%